Six Sigma in The Supply Chain (2019)
This article aims to present the state of art of the use of Six Sigma in the supply chain. As a result of the article, we identify a research opportunity related to the construction of a methodology to support the design and improvement of supply chains and logistics systems generically. Furthermore, we analyzed the opportunity of using the design of experiments and others statistical techniques in order to designor improve efficient processes with statistical basis.